Risk of hepatitis B reactivation in rheumatic patients receiving tocilizumab treatment (Annals of Medical Research, 2025)
Aim: This study aimed to investigate the relationship between tocilizumab, a biological agent widely used for treating rheumatic diseases, and hepatitis B virus reactivation (HBVr).Materials and Methods: The electronic records of all patients who received tocilizumab in our rheumatology outpatient clinic between July 2018 and August 2024 were retrospectively reviewed. Demographic data, baseline and followup HBV serological markers, liver biochemistry, and antiviral prophylaxis details were extracted and analyzed.Results: A total of 54 patients were included (76.2 % female; mean age 57.5 ± 14.3 years). While HBsAg, anti-HBc IgGG and anti-HBs were requested for all patients before treatment, HBsAg was positive in 1 of 54 patients (1.9%) and anti-HBc IgG was positive in 26 (48.1%). While antiviral treatment was initiated in 10 (18.5%) of the patients, 9 were HBsAg negative, 1 was HBsAg positive, and 1 was anti-HBc Ig G positive. No patient experienced HBV reactivation during treatment; however, one HBsAg-positive patient achieved HBsAg seroclearance. The mean follow-up period was 50.5 ± 22.9 months.Conclusion: No patient experienced HBV reactivation during tocilizumab therapy, and a single HBsAgpositive participant on prophylactic tenofovir achieved HBsAg seroclearance. These realworld data suggest that HBsAgnegative/antiHBcpositive individuals may be managed with vigilant biochemical and serological monitoring rather than routine antiviral prophylaxis during tocilizumab treatment. Nevertheless, the retrospective singlecentre design and modest sample size limit the strength and generalizability of these findings; larger prospective studies are required for definitive guidance.
Keywords: Rheumatological disease; Tocilizumab; Hepatitis B virus reactivation